Revisiting the Biclique Attack on the AES - Carvalho, G. C. de; Kowada, L. A. B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2023: Anais do XXIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2023.232855, 2023)
The AES Cipher is one of the most widely used block ciphers throughout the world for the better part of two decades now. Despite its relevancy, there has been no great progress in the attempts at finding exploitable flaws or cryptanalysis techniques that are able to find the secret key in less time than simple exhaustive search for its full version. The only exception is biclique cryptanalysis which was used more than once to recover the secret key in marginally less time than simple brute force. The last improvement happened 8 years ago. This paper finds the best results for all but one of the variations attempted on the AES, through the help of the concept of generator sets for related-key differentials, in terms of time complexity as well as a software that semi-automates tests on general word-based ciphers.